Experimental Modeling of Combined and Sequential Use of Transosseous and Intramedullary Blocking Osteosynthesis - E. A. Shchepkina (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. The introduction of the combined and sequential application of transosseous and intramedullary blocked osteosynthesis in limb lengthening requires an experimental study of the features of distraction regenerate. For small animals (in particular rabbits), special models are required.Aims. To develop experimental models of sequential and combined use of transosseous and intramedullary osteosynthesis in limb lengthening and substantiate their effectiveness.Materials and methods. A comparative study was carried out on 30 rabbits of the Soviet Chinchilla breed. Experimental models of sequential (EM-1) and combined (EM-2) application of transosseous and intramedullary osteosynthesis with preservation of the apparatus during the fixation period to simulate blockage were studied in the main groups. For comparison, sequential (comparison model 1 – CM-1) and combined (comparison model 2 – CM-2) use of transosseous and intramedullary osteosynthesis with dismantling of the apparatus at the end of distraction were modeled. The control was a regenerate formed according to the classical Ilizarov method. Radiographs were performed in dynamics, CT and morphological studies – at the end of the fixation period.Results. It was noted that regenerates of the same type in structure were formed in the EM-1 and CM-1 groups, as in the EM-2 and CM-2 groups. With successive methods, the spindle-shaped form of the regenerate prevailed, the formation of a pronounced periosteal component was noted. Powerful cortical plates, according to morphological studies, are formed from the periosteal and intermediate zones. With combined techniques, the cortical plates are formed thinner and predominantly from the periosteal component, the shape of the regenerate is closer to fusiform. In the comparison groups, the total time of surgical interventions was 25–50 % longer, in 50 % of cases there was a loss of length or deformation of the regenerate.Conclusions. The developed models of sequential and combined use of transosseous and intramedullary osteosynthesis for limb lengthening with preservation of fixation with an apparatus to simulate blocking have proven to be reliable in terms of fixation and easy to use on small laboratory animals..